Diálogo del saber campesino y la investigación científica: árboles nativos dendroenergéticos en la Reserva de la biosfera Sierra de Huautla, Morelos, México - Artemio Cruz León; Miguel Uribe Gómez; Alejandro Lara Bueno; César Augusto Yescas Albarrán; Ranferi Maldonado Torres (Revue d'ethnoécologie)
The farming communities of the Sierra de Huautla, keep tradition in using firewood, which is strong pressure on the native deciduous trees. Through participatory dialogue with housewives and loggers and their local knowledge, 6 tree species were selected with value fuelwood in order to design agroforestry technologies that promote the use and the preservation. The species are: tlahuitol [Lysiloma divaricatum (Jacq.) Willd.], tepehuaje [Lysiloma acapulcense (Kunth) Benth.], palo Brasil (Haematoxylum brasiletto H.Karst.), palo dulce [Eysenhardtia polystachya (Ortega) Sarg.], tecolhuixtle (Mimosa benthamii J.F.Macbr.) and cubata blanca [Acacia pennatula (Schltdl. & Cham.) Benth.]. The contents of dry matter, moisture, organic matter, ash, as well as the heat of combustion and wood density rates, indicators of the quality of the wood, were measured for these species. Tecolhuixtle is the most diminished species by its highly desirable characteristics as firewood; currently, cubata blanca presents intense extraction, although the best species of wood for housewives and loggers are tlahuitol and tepehuaje.